EP217609, a neutralisable dual-action FIIa/FXa anticoagulant, with antithrombotic effects in arterial thrombosis - Alame, Ghina; Mangin, Pierre H.; Freund, Monique; Riehl, Nadia; Magnenat, Stéphanie; Petitou, Maurice; Hechler, Béatrice; Gachet, Christian (Thrombosis and Haemostasis, 2015)
EP217609 is a new synthetic parenteral dual-action anticoagulant combining a direct thrombin inhibitor (α-NAPAP analog), an indirect factor Xa inhibitor (fondaparinux analog) and a biotin moiety allowing its neutralisation. EP217609 exhibited similar in vitro anticoagulant properties as its parent compounds. On the basis of dose-response curves, we identified low and moderate doses of EP217609 resulting in similar ex vivo prolongation of the APTT as α-NAPAP analog and comparable ex vivo anti-FXa activity as fondaparinux. The effects of EP217609 were compared to those of its parent compounds used alone or in combination in two models of experimental thrombosis induced by FeCl3 injury of the carotid artery or mechanical injury of atherosclerotic plaques in ApoE-deficient mice. When administered at low doses increasing the APTT by only 1.1 fold, EP217609 significantly reduced the thrombus area in both models as compared to α-NAPAP analog or fondaparinux alone, but not to the combination of these drugs. In contrast, at higher doses increasing the APTT 1.5 times, EP217609 was not superior to either parent compound. Low doses of EP217609 did not prolong the tail bleeding time or increase the volume of blood loss, although a tendency towards an increased blood loss was observed in five out of 12 mice. Finally, the effects of EP217609 could be neutralised in vivo by injection of avidin. The pharmacological profile of EP217609, its performance in arterial thrombosis models and its possible neutralisation make it an interesting molecule and a potential candidate as an antithrombotic drug.
Keywords: Animal models; antithrombin; arterial thrombosis; atherothrombosis; coagulation inhibitors